Strategi Politik Partai Persatuan Pembangunan (PPP) Pada Pemilu Legislatif Kabupaten Pemalang Tahun 2014 - Ahmad Nafis Junalia; Suwanto Adhi; Lusia Astrika (Journal of Politic and Government Studies, 2015)
This research discusses the political strategy of  united development party on legislative elections in pemalang regency in 2014. Method used in this research is qualiltative approach. The data are obtained through depth interviews to each informant continued to analyze them comprehensively. The results of this research explains some succesful results of political strategies applied by United Development Party (PPP) through, namely: Political Campaign, Prominent Figure, Base Mass, Introducing Cadre Popular, Community Approach, and General Strategy. Based on the vote on legislative elections in Pemalang regency in 2014 United Development Party got six seats of  DPRD  in Pemalang regency in period of  2014 – 2019, which in each constituency they have been  represented by legislative candidate of  United Development Party from six constituencies.The results is  appropriate with the target targeted by Branch Leader Council (DPC) of United Development Party (PPP) of  Pemalang regency, namely getting six seats of DPRD of Pemalang regency in every constituency from six constituencies. It has been represented by every legislative candidate of United Development Party (PPP) who passes as legislative member in period of  2014 – 2019.